The structure of graphs with forbidden induced C_4, C_4, C_5, S_3, chair and co-chair - Salman Ghazal (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2018)
We find the structure of graphs that have no C4, C_4, C5, S3, chair and co-chair as induced subgraphs. Then we deduce the structure of the graphs having no induced C4, C_4, S3, chair and co-chair and the structure of the graphs G having no induced C4, C_4 and such that every induced P4 of G is contained in an induced C5 of G.